Commodifying Taste: An Autoethnography of Free Labour, Exploitation and Alienation on Spotify - Owen, Charles (New Explorations)

(untitled) (New Explorations Association, 2023)
The purpose of this paper is to critically analyze the business and marketing practices of the music streaming service Spotify. The paper demonstrates that Spotify’s features are designed to elicit free labour from its users so that Spotify may exploit this labour, alienate its users from the products of this labour, and ultimately reap the maximum benefits from this labour. This is accomplished primarily through the attachment of marketing to, or the commodification of, the social and affectual roles that music plays in the human experience, such as allowing individuals to forge bonds over shared music taste. Spotify benefits from these practices in numerous ways, such as the obtaining of user data that betters the platform’s algorithm and attracts paying targeted marketers, or the propagation of free and effective marketing for the service undertaken by users. The processes by which these benefits are realized also, in many cases, act in a cyclical nature, perpetuating themselves. The end goal of this paper is to bring academic attention to the specific forms of free labour, exploitation and alienation occurring on Spotify in an effort to lay groundwork for the development of alternatives.